Impact of the Second Epidemic Wave of SARS-CoV-2: Increased Exposure of Young People - Lisandru Capai; Shirley Masse; Toscane Fourié; Dorine Decarreaux; Jean Canarelli; Marie-Helene Simeoni; Abdennour Amroun; Souand Mohammed-Ali; Paola Mariela Saba Villarroel; Xavier de Lamballerie; Rémi Charrel; Alessandra Falchi (Frontiers in Public Health, 2021)
We aimed to use serological surveillance based on serial cross-sectional sampling of residual sera obtained from clinical laboratories to compare the differences in age and sex profiles of infected persons in the first and second waves of SARS-CoV-2 in Corsica, France. Residual sera were obtained, including samples from individuals of all ages collected for routine screening or clinical management by clinical laboratories. All the sera collected were tested for the presence of anti-SARS-CoV-2 IgG using a kit for semi-quantitative detection of IgG antibodies against the S1 domain of the viral spike protein (ELISA-S). Samples that were borderline and positive in ELISA-S were tested with an in-house virus neutralization test. During the second-wave period, we collected between 6 November, 2020 and 12 February, 2021, 4,505 sera from patients aged 0–101 years (60.4% women). The overall weighted seroprevalence of residual sera collected during the second-wave period [8.04% (7.87–9.61)] was significantly higher than the overall weighted seroprevalence estimated at the end of the first wave between 16 April and 15 June, 2020 [5.46% (4.37–7.00)] (p-value = 0.00025). Ninety-eight (30.1%) of the 326 samples tested in the VNT assay had a positive neutralization antibody titer. Estimated seroprevalence increased significantly for men [odds ratio (OR) OR = 1.80 (1.30–2.54); p-value = 0.00026] and for people under 30 years of age [OR = 2.17 (1.46–3.28); p-value = 0.000032]. This increase was observed in young adults aged 20–29 years among whom antibody frequencies were around four-fold higher than those observed at the end of the first wave. In conclusion, our seroprevalence estimates, including the proportion of the participants who had produced neutralizing antibodies, indicate that in February, 2021 the population of Corsica was still far from being protected against SARS-Cov-2 by “herd immunity.”